Estudo do transporte de íons Li+ em híbrido orgânico-inorgânico (SPHP) e nanocompósito (NHP) e seu desempenho em dispositivos eletrocrômicos - Souza, Flávio Leandro de (2006)
The main goal of the present work is to describe the lithium ion transport mechanism in a hybrid (SPHP) and nanocomposite (NHP) polyelectrolyte based on complex conductivity analysis as a function of temperature. The chemical synthesis strategy used to produce a helical free-chain configuration of singlephase hybrid organic-inorganic polymer electrolytes was based on a simple non-hydrolytic sol-gel route. The SPHP resulting from this strategy showed a Tg of -79oC and its temperature-dependent ionic conductivity (achieved at temperatures higher than Tg) displayed an Arrhenius behavior. This remarkable behavior characterizes a segmental motion-decoupled polymer. An Arrheniustype behavior for ionic conductivity (σdc) and hopping frequency of charge carrier (ωp) were observed. The values of activation energy obtained for σdc and ωp as a function of the temperature was approximately the same (~ 0.2 eV), indicating that the dispersive conductivity, σ(ω), originates from the migration of ions. This relevant physical aspect is allied to the fact that the contribution to the dispersive conductivity appears to be governed by a nearly frequency independent dielectric loss, ε = A, which correspond to an almost linear frequency dependent term of the form, σ = ωε ( ω) = Aω, in the real part of the complex conductivity. Furthermore, we observe a high stability, of SPHP and NHP when applied in a large EC device (5 x 10 cm2) using WO3 (electrochromic) and CeO2 -TiO2 (counter-electrode ion storage) electrodes, both optimized and produced by Leibniz-Institut of New Materials (Leibniz-INM, Germany). The electrochromic device exhibited excellent color and bleach reversibility, high coloration efficiency (> 35cm2 / C) from the first cycle up to more than 60000 CA cycles, and a maximum constant rate of deintercalation / intercalation (Oout / Qin = 1). Its remarkable behavior and high stability render this material an excellent candidate for application in electrochromic devices.